2018
DOI: 10.3892/mmr.2018.9741
|View full text |Cite
|
Sign up to set email alerts
|

A GLP‑1 receptor agonist attenuates human islet amyloid polypeptide‑induced autophagy and apoptosis in MIN6 cells

Abstract: Type 2 diabetes mellitus (T2DM) is characterized by the dysfunction and loss of pancreatic islet β-cells, in part due to islet amyloid deposits derived from islet amyloid polypeptide (IAPP). The glucagon-like peptide-1 (GLP-1) receptor agonist exendin-4 enhances the insulin secretory response by increasing β-cell mass in T2DM. However, it is unknown whether exendin-4 protects β-cells from IAPP-mediated autophagy and apoptosis. In the present study, reverse transcription-quantitative polymerase chain reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Only a limited number of studies have investigated the potential impact of GLP-1RA on IAPP toxicity. Exendin-4 alleviated h-IAPP-induced apoptosis in MIN6 [ 191 ] and in INS-1E [ 192 ] beta-cell lines, in islets from h-IAPP transgenic mice [ 193 ] or in human islets [ 194 , 195 ]. The protection was not associated with a reduced formation of h-IAPP deposits [ 192 ], but with increased levels of AKT phosphorylation [ 192 , 193 , 194 , 195 ].…”
Section: Molecular Mechanisms Induced By Glp-1 To Protect Beta-cells From Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Only a limited number of studies have investigated the potential impact of GLP-1RA on IAPP toxicity. Exendin-4 alleviated h-IAPP-induced apoptosis in MIN6 [ 191 ] and in INS-1E [ 192 ] beta-cell lines, in islets from h-IAPP transgenic mice [ 193 ] or in human islets [ 194 , 195 ]. The protection was not associated with a reduced formation of h-IAPP deposits [ 192 ], but with increased levels of AKT phosphorylation [ 192 , 193 , 194 , 195 ].…”
Section: Molecular Mechanisms Induced By Glp-1 To Protect Beta-cells From Apoptosismentioning
confidence: 99%
“…A reduced JNK activation has not always been noticed [ 192 , 195 ], and exendin-4 protection from h-IAPP toxicity does not seem to alleviate ER stress in INS-1E cells [ 192 ]. Finally, an improvement of the autophagic flux by exendin-4 was reported in MIN6 cells overexpressing h-IAPP [ 191 ].…”
Section: Molecular Mechanisms Induced By Glp-1 To Protect Beta-cells From Apoptosismentioning
confidence: 99%
“…Liraglutide is a glucagon-like peptide-1 (GLP-1) analog that binds to the GLP-1R receptor and has been shown to be abundantly expressed by RGC-5 cells (4). A GLP-1 homolog, exendin , is 53% similar in sequence homology and is commonly utilized as a GLP-1 receptor antagonist in experimental studies (5). Zhang et al reported Glp1r expression on retinal ganglion cells and investigated the GLP-1 protective mechanisms against hyperglycaemic conditions (6).…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by glucose and lipid metabolism disorders, which are mainly characterized by decreased number, hypofunction and increased apoptosis of pancreatic β-cells. It has been shown that the mechanisms involved in the development of T2DM caused by multidimensional pathogenic responses in pancreatic β-cells include pathological processes such as cell iron death, endoplasmic reticulum (ER) stress, reactive oxygen species activation, membrane disruption, and receptor-mediated signaling impairment transduction cascades [1]. Iron metabolism plays an important role in the development and progression of a variety of metabolic diseases, especially T2DM.The first case to investigate the relationship between iron metabolism and diabetes is hereditary hemochromatosis (HH), and the specific mechanism of HH-associated diabetes pathogenesis remains incompletely clarified, and insulin deficiency and insulin resistance (IR) may be important contributing factors.…”
mentioning
confidence: 99%